Qualitative study of Determinants of Environmental Culture - Zahra Hemmati; Mahdieh Rezaei; Seyed Mohammad Shobeiri (توسعه اجتماعی)
Today, environmental issues and problems have become many challenges and concerns for society. Many believe that these problems stem from cultural weakness. Bourdieu sees the root of environmental crises in the Western worldview, which has a hegemonic view of the environment. In fact, without the formation of environmental culture, the formation of a society with high environmental responsibility is not possible. Therefore, in the present study, a qualitative study of the determinants of environmental culture was performed. Using qualitative method and semi-structured interviews with 15 experts, data were collected and then content analysis was performed. Finally, two comprehensive themes and five organizing themes were achieved. Regarding the components of environmental culture, 7 basic themes were obtained, which could be divided into comprehensive and organizing themes. These basic themes were divided into two general categories: subjective and objective. Regarding the factors affecting environmental culture, 12 basic themes were mentioned, which could be divided into comprehensive and organizing themes. These basic themes were divided into three general categories: socio-cultural factors, motivational factors and economic factors. Finally, in order to check the content validity of the model, the CVR index was used, the results of which indicate the approval of the model designed by experts.